2014
DOI: 10.1021/ie503606y
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of Both Kaolin and Hematite Suspensions Using the Starch-Based Flocculants and Their Floc Properties

Abstract: In this work, two kinds of starch-based flocculants with the same chemically modified functional groups but far different substitution degrees, (2-hydroxypropyl)trimethylammonium chloride etherified carboxymethyl starch (denoted as CMS-CTA-P and CMS-CTA-N, respectively) were successfully prepared. CMS-CTA-P and CMS-CTA-N bear opposite surface charge properties in water under most of the measured pH range. The flocculation performance of these two flocculants has been systematically studied using kaolin and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 48 publications
0
21
0
2
Order By: Relevance
“…Several studies have shown that naturally occurring coagulants/flocculants can be used for the treatment of effluents and drinking water [5,12,16]. ese natural coagulants/flocculants, in contrast to synthetic ones, are more accessible and nontoxic [17,18]. All those advantages justify the actual rising interest for natural coagulants [12,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that naturally occurring coagulants/flocculants can be used for the treatment of effluents and drinking water [5,12,16]. ese natural coagulants/flocculants, in contrast to synthetic ones, are more accessible and nontoxic [17,18]. All those advantages justify the actual rising interest for natural coagulants [12,13,19].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the effectiveness for two types of starch-based flocculants by Haijiang Li et al (2015), suspensions of hematite and kaolin, whose charge is opposite to that of flocculants, were used. Based on the change in ζ-potential of the particles was found to be the main mechanism of clarification in this case was the neutralization of particle's charge.…”
Section: Fig 2 Curves Of the Percentage Deposition Of Suspended Parmentioning
confidence: 99%
“…Large numbers of cationic flocculants have been utilized for flocculation of kaolin. Li et al . have used starch‐based cationic polymer for kaolin flocculation.…”
Section: Introductionmentioning
confidence: 99%